Targeted Delivery of Anti-Inflammatory Agents to Tumors - Coimbra, Maria; Kuijpers, Sylvia A.; van Seters, Sebastiaan P.; Storm, Gert; Schiffelers, Raymond M. (Current Pharmaceutical Design, 2009)
Inflammation is considered a hallmark of cancer. The chronic inflammatory process is driven by the interaction of cells, proteins, cytokines, transcription factors, and lipid mediators within the tumor microenvironment giving rise to complex pro-inflammatory cascades. These can be inhibited by a variety of different anti-inflammatory compounds, like non-steroidal anti-inflammatory drugs, glucocorticoids, anti-inflammatory biologicals, phytotherapeutics (mainly polyphenols), and drugs with pleiotropic anti-inflammatory effects. In general, it appears that the anti-tumor activity of these compounds occurs at higher doses than the doses used in conventional anti-inflammatory therapy. To optimally take advantage of the anti-tumor activity and at the same time limit side effects, targeted delivery of anti-inflammatory drugs appears an attractive approach.